Incidence of intraoperative hearing loss during middle cranial fossa approach for repair of superior semicircular canal dehiscence. (August 2018) - Johanis, Michael; Yang, Isaac; Gopen, Quinton
Highlights: Superior semicircular canal dehiscence is a rare inner ear disorder. Significant debate exists between the middle fossa and transmastoid surgical options. Brainstem auditory evoked potentials can detect hearing loss changes intraoperatively. UCLA holds the largest cohort of patients with superior semicircular canal dehiscence. This study demonstrates a low risk of hearing loss via the middle fossa approach. Abstract: Introduction: Superior semicircular canal dehiscence is a rare inner ear disorder characterized by an abnormal third opening between the superior semicircular canal and middle fossa. Symptoms include amplification of internal sounds, aural fullness, tinnitus, hearing loss, autophony, sound-induced vertigo (Tullio phenomenon), pressure-induced vertigo (Hennebert sign), disequilibrium, nystagmus, oscillopsia, and headache. While no cure exists for SSCD, surgical treatment has proven to effectively minimize these symptoms. This study reviewed brainstem auditory evoked potentials (BAEPs) that were monitored intraoperatively to better understand hearing loss risks associated with surgical treatment for SSCD. Methods: A retrospective chart review was conducted at the University of California, Los Angeles on adult patients with a confirmed diagnosis of SSCD who had undergone a middle cranial fossa repair from March 2011 to October 2017. A total of 142 cases of SSCD in 118 patients were repaired. Results: The majority of patients' BAEPs remained stable and had no intraoperative hearing changes (n = 135; 95.1%). Seven patients experienced intraoperative changes as determined by a prolongation and reduction of Wave V latency (4.9%). Of these seven cases, five experienced a return to baseline prior to the end of surgery, and had no post-operative changes in hearing (71.4%). Overall, only two of the 142 surgeries (1.4%) resulted in failure to normalize and, as such, these patients experienced permanent changes in hearing. Conclusion: The results of this retrospective review demonstrate a low risk for hearing loss due to SSCD surgery via the middle fossa craniotomy approach.